Pengaruh Pembiayaan Kur Dan Ease Of Doing Bussiness (Eodb) Melalui Pendapatan Serta Dampaknya Terhadap Kesejahteraan (Studi Kasus Pada UMKM di Kota dan Kabupaten Tasikmalaya) - Zahra Virliana, Nadya; Widian Prahasti, Tika; Damayanti, Momy (EKOBIMA, 2025)
The government through its various programs stimulates MSME actors to develop and gain prosperity in their lives. MSMEs that are encouraged to grow in terms of quality and quantity by the current government through financial inclusion programs have an important role in the economy of a country. This study examines the effect of KUR financing and EODB through income on the welfare of MSMEs in Tasikmalaya. The object of research is the perpetrators of MSMEs in Tasikmalaya as many as 80 people. The regression equation model with the path model from this study is divided into 2 sub structures, namely Y = 0.568X1 + 0.523X2 + 0.609 and Z = 0.523Y + 0.626. The conclusion of this study is that there is a partially significant effect between KUR financing through income on welfare of 29.7%, respectively, there is no significant effect of EODB through income on welfare and there is a significant effect of 80.8% simultaneously between KUR financing and EODB through income for the welfare of MSMEs in Tasikmalaya.